GOOD CORPORATE GOVERNANCE DENGAN NILAI PERUSAHAAN YANG DIMODERASI OLEH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN SUBSEKTOR ASURANSI - Khodijah, Ina; Denardo, Denardo (Gapenas Publisher, 2023)
This study aims to examine the effect of good corporate governance on company value with corporate social responsibility as a moderation variable. Primary data processing using path analysis techniques using SMART PLS 4 software. The results showed that good corporate governance affects corporate value, and corporate social responsibility affects company value while corporate social responsibility is unable to mediate good corporate governance on company value